Biomimetic aquaporin membranes for osmotic membrane bioreactors: Membrane performance and contaminant removal. (February 2018) - Luo, Wenhai; Xie, Ming; Song, Xiaoye; Guo, Wenshan; Ngo, Hao H.; Zhou, John L.; Nghiem, Long D.
Highlights: Aquaporin FO membrane showed better transport properties than conventional membranes. Aquaporin FO membrane resulted in less salinity build-up in OMBR operation. Aquaporin FO membrane exhibited stable performance in OMBR operation. Excellent contaminant removal by OMBR was achieved with the aquaporin membrane. Abstract: In this study, we investigated the performance of an osmotic membrane bioreactor (OMBR) enabled by a novel biomimetic aquaporin forward osmosis (FO) membrane. Membrane performance and removal of 30 trace organic contaminants (TrOCs) were examined. Results show that the aquaporin FO membrane had better transport properties in comparison with conventional cellulose triacetate and polyamide thin-film composite FO membranes. In particular, the aquaporin FO membrane exhibited much lower salt permeability and thus smaller reverse salt flux, resulting in a less severe salinity build-up in the bioreactor during OMBR operation. During OMBR operation, the aquaporin FO membrane well complemented biological treatment for stable and excellent contaminant removal. All 30 TrOCs selected here were removed by over 85% regardless of their diverse properties. Such high and stable contaminant removal over OMBR operation also indicates the stability and compatibility of the aquaporin FO membrane in combination with activated sludge treatment.